Microscopic Anatomy of Liver in Cats of Tirunelveli Region - S. Rajathi; Pranavjith; A Priyanka3; N. Priyadharshini; S Priya Kanishka; Shanthini S. (Indian Journal of Veterinary Anatomy, 2026)
The liver of cat comprised of six lobes namely left lateral, left medial, quadrate, caudate, right lateral and right medial. The livers were collected from six freshly dead cats presented for post-mortem examination. The liver was cut into small pieces, fixed and routine histological processing was done and paraffin blocks were prepared. The paraffin sections of 3-5 micrometer thickness were cut and stained. The liver was the compound tubular gland with a layer of connective tissue capsule enclosing the parenchymatous tissue. The liver consisted of capsule, septa and lobules. The arrangement of hepatocytes in the lobule was in radiating cords. Hepatic sinusoids were observed between the hepatic cords. The hepatocytes were polygonal in shape with vacuolated eosinophilic cytoplasm. The dark blue stained nuclei were centrally located with single dot shaped nucleoli. The sinusoids were lined by single layer of flat squamous sinusoidal endothelial cells with flat centrally located nucleus. The sinusoidal lumen also contained Kupffer cells along with blood cells. The central vein was located at the centre of the hepatic lobule with narrow to wide lumen. The portal areas were observed at the corners of the hepatic lobule with branches of the hepatic artery, portal vein and bile duct. The size of the bile duct was from small to large in different portal areas.